2009
DOI: 10.1371/journal.pone.0005756
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidic Endothelium for Studying the Intravascular Adhesion of Metastatic Breast Cancer Cells

Abstract: BackgroundThe ability to properly model intravascular steps in metastasis is essential in identifying key physical, cellular, and molecular determinants that can be targeted therapeutically to prevent metastatic disease. Research on the vascular microenvironment has been hindered by challenges in studying this compartment in metastasis under conditions that reproduce in vivo physiology while allowing facile experimental manipulation.Methodology/Principal FindingsWe present a microfluidic vasculature system to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
284
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(286 citation statements)
references
References 52 publications
2
284
0
Order By: Relevance
“…For example, a recent in vitro study identified changes in endothelial myosin light chain kinase upon tumor-endothelial cell contact (16), however this method did not allow for measurement of endothelial permeability or the accurate control of the microenvironmental stimuli. Compared to other in vitro models (16,21) and microfluidic models of tumor-endothelial interactions (25,35), our assay provides a number of unique features, such as high-resolution live cell imaging, the formation of an endothelial monolayer on a 3D ECM enabling us to model intravasation, and for precise quantification and control of critical tumor microenvironmental factors. The readily accessible apical side of the endothelium allows for the introduction of cell types in the tumor microenvironment, such as macrophages, the precise establishment of growth-factor gradients, fluid flow, and real-time spatially resolved endothelial barrier function measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a recent in vitro study identified changes in endothelial myosin light chain kinase upon tumor-endothelial cell contact (16), however this method did not allow for measurement of endothelial permeability or the accurate control of the microenvironmental stimuli. Compared to other in vitro models (16,21) and microfluidic models of tumor-endothelial interactions (25,35), our assay provides a number of unique features, such as high-resolution live cell imaging, the formation of an endothelial monolayer on a 3D ECM enabling us to model intravasation, and for precise quantification and control of critical tumor microenvironmental factors. The readily accessible apical side of the endothelium allows for the introduction of cell types in the tumor microenvironment, such as macrophages, the precise establishment of growth-factor gradients, fluid flow, and real-time spatially resolved endothelial barrier function measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, modeling the tumor microenvironment by integrating the interactions among multiple cell types with biochemical and biophysical factors is a very attractive target for microfluidics. Toward this end, a number of microfluidic designs have been developed to study growth-factor gradients in cancer cell migration (22,23), tumor-stromal cell interactions (24), and tumor-endothelial cell interactions (25).…”
mentioning
confidence: 99%
“…Others have detailed the process by which porous membranes are incorporated into microdevices 7,12,23 and demonstrated their utility for biological studies. 7,8,12,24,25 For the devices used in this study, the top straight channel and bottom S-shaped channel were 2000 m wide by 300 m high.…”
Section: A Device Fabricationmentioning
confidence: 99%
“…These models have been used to study the interactions between the endothelium and other cells, such as leukocytes or cancer cells. [30][31][32][33][34][35][36] However, most current microfluidic blood vessel models only provide a controlled environment for adhesion of individual cancer cells to the endothelium under stimuli. Limited information is available regarding the interaction of tumor aggregates and endothelium, as well as the subsequent events (such as transendothelial invasion or proliferation in situ) that follow adhesion.…”
Section: Introductionmentioning
confidence: 99%